Listening to climate change in my backyard: the frequency of overwintering Eurasian Blackcaps Sylvia atricapilla increased in a small town in Northern Italy, but not that of European Robins Erithacus rubecula (Avocetta, 2025)
Climate change is reshaping biotic communities all over the world, and birds are often affected by climate variations, including outside the most investigated breeding season. Here, using an opportunistic but intensive data collection, I show how the frequency of overwintering Eurasian Blackcaps Sylvia atricapilla has increased in recent winters (since 2011-2012) in an area in northern Italy where it used to be very rare during the coldest months of the year. A linear model based on time progression explained more than half of the variation of the species’ frequency. An alternative linear model based on the average daily temperature in the period December-February had a substantially similar (marginally better) performance, suggesting that such an increase could be driven by milder winter temperatures. A regular and abundant wintering species, the European Robin Erithacus rubecula, only showed fluctuations over the same period but not a temporal trend, nor a relation with average daily temperature. Given that the sampling effort was the same for the two species, finding a clear trend in Blackcaps but not in Robins pointed towards a real increase in the overwintering frequency of the former, rather than at sampling biases. This worked example also suggests that citizen science and opportunistically collected data could be potentially used to assess the effects of climate change on fine-scale, local variations in bird distribution, especially if collected in areas or contexts that are regularly visited by observers. Similar considerations may apply to passive/automated recorders.